Enhancing Students’ Speaking Skill through the Show and Tell Technique - Wardani, Marshela Tri (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2024)
Speaking is critical for junior high school students alongside listening, reading, and writing. However, problems in teaching speaking, such as limited vocabulary and low participation rates, expectedly emerged as observed at an Islamic junior high school. This study explores the effectiveness of the "Show and Tell" method in improving students' speaking abilities through classroom action research (CAR). The research shows significant improvement in speaking skills across two cycles. In the first cycle, scores increased from 57.47 to 70.42, highlighting progress despite the initial challenges. Several modifications were done in the second cycle, such as using pictures instead of objects. This further boosted engagement and comprehension and raising the scores to 86.02. Based on the finding, this study underscores the value of innovative teaching methods like "Show and Tell" which has proven its effectiveness in enhancing students’ speaking proficiency. It provides insights for educators who seek to improve language learning outcomes through student-centered approaches, fostering confidence and proficiency in communication skills.